An assessment of the clinical acceptability of direct acoustic cochlear implantation for adults with advanced otosclerosis in the United Kingdom - Kitterick, Pádraig T.; Reddy-Kolanu, Guna; Baguley, David; Lavy, Jeremy; Monksfield, Peter; Banga, Rupan; Ray, Jaydip; Snik, Ad; O'Donoghue, Gerard (Lippincott Williams & Wilkins, 2017)
Hypothesis: Assess the clinical acceptability of direct acoustic cochlear implantation for patients with advanced otosclerosis and the support for conducting a controlled trial of its effectiveness in the United Kingdom.